Development of Integrated Competency-Based Physics Academic Test for Teacher Professional Education Program Students - Sujito, Sujito; Ekawati, Ratna; Pratiwi, Hestiningtyas Yuli (Teaching, Learning, and Development, 2026)
The teacher professional education program requires prospective physics teachers to demonstrate integrated academic, pedagogical, social, and personal competencies. However, current evaluation practices remain dominated by traditional multiple-choice tests that primarily assess lower-order cognitive skills and fail to capture critical thinking, problem-solving, and reflective abilities. This study aims to develop a problem-based professional competency test designed to predict the academic success of the teacher professional education program students in physics. The research employed a Research and Development (R&D) approach with a modified Borg & Gall model, covering needs analysis, design, expert validation, pilot testing, revisions, and field trials. The participants were 57 physics students of the teacher professional education program on universitas in Malang at 2025. The initial instrument consisted of 35 items, which were refined to 25 valid items through rigorous analysis of validity, reliability, item difficulty, discrimination power, and distractor effectiveness. Findings revealed that all 25 items were valid, with an instrument reliability coefficient of 0.788. The distribution of item difficulty was dominated by easy to moderate levels, ensuring a balanced measurement range. These results highlight that a problem-based professional competency test can serve as a valid, reliable, and contextually relevant evaluation tool. It not only aligns with the demands of higher-order thinking but also reflects the pedagogical readiness required of future physics teachers.